2015
DOI: 10.1002/pc.23693
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on low velocity impact damage of laminated composites toughened by structural toughening layer

Abstract: The intralaminar and interlaminar damages of U3160/ 3266 laminated composites toughened by polyamide nonwoven fabric (PNF) under low velocity impact are investigated through a numerical model which considers both the three-dimensional continuum damage mechanics (CDM) and the bilinear cohesive zone model (CZM). The analysis of the intralaminar damage is implemented by the ABAQUS/Explicit finite element code coupled with a user-defined subroutine VUMAT where the longitudinal failure, transverse matrix cracking, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Carbon fiber/epoxy (CF/EP) laminated composites with light weight, good tensile performance, low cost, and ease of operation are widely used in various fields, including the automotive, aerospace, and petrochemical industries [1,2,3,4]. However, poor interlaminar strength is an inherent drawback of any laminated composite due to its low delamination resistance and damage tolerance, particularly under impact loading; this condition significantly reduces the load bearing capacity of laminated composites [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber/epoxy (CF/EP) laminated composites with light weight, good tensile performance, low cost, and ease of operation are widely used in various fields, including the automotive, aerospace, and petrochemical industries [1,2,3,4]. However, poor interlaminar strength is an inherent drawback of any laminated composite due to its low delamination resistance and damage tolerance, particularly under impact loading; this condition significantly reduces the load bearing capacity of laminated composites [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This reveals the different damage modes and delamination areas presently obtained from this study. Similarly, Sun et al performed experimental and numerical studies to investigate the effects of interlayer toughening by polyamide nonwoven fabric (PNF) on damage characteristics of U3160/3266 laminated composites. It was indicated that damage area was significantly decreased with decreasing interlayer thickness or strength of toughened fiber.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical parameters shown in Table 1 were obtained through standard testing methods, except for some lamina properties ( ν 12 , ν 23 , G 23 , S 23 , G ft , G fc , G mt , and G mc ) and interlaminar properties of Control ( E , G , σn0, and σs0), which were cited from the literature. [ 33,35 ]…”
Section: Numerical Simulationmentioning
confidence: 99%
“…These constitutive models are briefly introduced in this study, and for more details, please refer to our previous work. [ 33 ] Intralaminar damage is implemented in the user subroutine VUMAT. The 3D Hashin failure criterion is employed to predict the damage initiation of various intralaminar damage modes, as described below.…”
Section: Numerical Simulationmentioning
confidence: 99%